Mamamayan muna, hindi mamaya na [videorecording] - Philippines Civil Service Commission. Institute for Filipino Cinema (Institute for Filipino Cinema, 1994)
A government-wide campaign of the Civil Service Commission that addresses the need for behavioral reforms in the bureaucracy, particularly in the manner by which civil servants deal with the public